Service quality and delivery in banking services—An Indian perspective - Abhinav Gupta (Cogent Business & Management, 2016)
The banking service industry has experienced great change in recent decades. The present study covers the domains of Job satisfaction of employees and its impact on the service quality delivered by them. Exploring further the construct of employee job satisfaction amongst the three groups of banks, an attempt that is unique to this research, one finds that as expected, there is a difference between the three groups of banks in terms of the job satisfaction levels experienced by them. The overall job satisfaction is reported to be the highest amongst the PSU bank employees. The private and foreign bank employees are less satisfied compared to their counterparts working in PSU banks. Context job satisfaction factors (i.e. satisfaction with pay, variety of activities, environment and security) are more descriptive of employee job satisfaction than the content factors (i.e. satisfaction with work, customer interaction and promotion). In the case of PSU bank employees, the opportunity to interact does not contribute to the overall job satisfaction in the regression analysis. One striking result is that marital status is a significant contributor to overall job satisfaction of employees with married employees being more satisfied than the unmarried ones. The aspect of salary (pay) has the least contribution to the overall job satisfaction. This is a positive result in the sense that employees will not be influenced by higher pay offers from competitors but also draw the attention of the bank to the significant factors like environment, variety of activities that are major contributors to job satisfaction.
Keywords: 650